Un guide colonial. Le Guide du Voyageur au Congo belge et au Ruanda-Urundi - Henri Nicolaï (Belgeo)
The Travel Guide to Belgian Congo and Ruanda-Urundi, of which five editions were released during the last ten years of Belgian Congo, is an archetypal colonial guide.The paper first highlights the emergence and the features of tourism in Central Africa. Congolese tourism, long fascinated with the myths of the Mountains of the Moon and the Source of the Nile, is essentially elitist and mainly centred on sport-hunting. Mountain gorillas, Ruwenzori climb, Tutsi dancers, Albert National Park, and Wagenia fishermen are considered the icons of this tourism first attracted by the Kivu and the Great Lakes and later the Katanga. The very first edition of the guide by Vicicongo in the 1930s is precisely entitled Congo-Nile. All these myths and settings are shown in some famous American adventure movies of the early 1950s.In the second part, the paper describes the genesis of the Guide, its main features, its plan and contents. Produced by the Colony’s official information services, the Guide describes the persistence and the results of Belgium’s civilizing role. Claiming that Congo is no country of art and history, it gives natural environment a preponderant place and provides a truncated picture of Congo’s history, reflecting the biases of that time concerning the people. This makes it a highly significant document.The paper ends with some reflections and attempts by a reporter from Canvas TV channel and a photographer from Magnum to use the 1958 Guide to roam across the country a half-century later.